Towards transparent data access with context awareness - Wrzeszcz, Michał; Słota, Renata; Kitowski, Jacek (Wydawnictwa AGH, 2018)
Open-data research is an important factor accelerating the production and analysis of scientific results as well as worldwide collaboration, still, very little data is being shared at scale. The aim of this article is to analyze existing data-access solutions along with their usage limitations. After analyzing the existing solutions and data-access stakeholder needs, the authors propose their own vision of a data-access model.
Computer Science
Bibliogr. s. 216-220.
Keywords: distributed; transparent data access; distributed data storage; context awareness